Ranking of 5Cs in credit evaluation and bankers' perception of commercial bank lending to Malaysian small-scale farmers - Ghuslan, Mohamad Iruwan (2011)
The success of small farmers in business depends on their ability to tap credit, especially from commercial banks. The credit obtained from commercial banks can help farmers to modernize their agricultural activities (Bhat, 1982; Asiedu and Fuso, 2003). Therefore, there is a greater need for the commercial banks to provide credit to this vital sector of the economy since commercial banks are the largest and the most important credit institutions in Malaysia. However, the importance of Malaysian commercial bank as a source of financial to small agricultures has been less emphasized. Thus, the number of approved loans given to small farmers by Malaysian commercial banks is still considerably low due to the asymmetric information problems between the bankers and farmers. Therefore, the first objective of this study is to examine the importance of 5Cs credit evaluation on bank lending to the small-scale farmers. These 5Cs of credit evaluation have been reviewed in previous literatures to help banks evaluate borrower’s creditworthiness. Second, this study also attempts to analyze the commercial bankers’ perceptions on lending decisions to small-scale farmers. To achieve the objectives of the study, two different sets of data are collected, which consist of survey and interview sessions. A total of 202 respondents (bank branches) randomly selected from the peninsular of Malaysia while the interview sessions were conducted with fifteen credit officers and credit managers. To determine the relationship between the 5Cs of credit evaluation, banker’s perception and agricultural lending decisions, this study uses the Multiple Regression Analysis (MRA) to test the hypotheses. The findings suggest that the five predictor variables which is character, capacity, condition, capital, and bankers’ perceptions significantly influence the bank lending decision to small-scale farmers except for collateral. The results of this study show that capital is the most important rank of 5Cs in influencing the lending decision to small-scale farmers followed by condition, capacity, character and collateral. Apart from the importance of 5Cs, the result also shows that banker’s perception gets the highest beta coefficient among variables selected confirms that not only 5Cs may influence on lending decision but also most importantly is the banker’s perception. Despite the importance of 5Cs credit evaluation to overcome the problem of asymmetric information between banker and farmer which would improve the number of loan granted to this sector, loans given by commercial banks to the agricultural sector is still low. Therefore, to increase the number of loan to this sector, this study may suggest a few policies and strategies that will benefit many parties including banks, government as well as farmers. First, this study suggests commercial banks to maintain 5Cs credit evaluation with some adjustment to suit the farmer’s ability, credibility and financial standing. Secondly, the government should also allocate more funds and incentives equally to both Agro Bank and commercial banks and should ensure that small-scale farmers have access to these incentives at a lower cost and in a more effective way similar to the ones provided by Agro Bank. Thirdly, the commercial banks are required to extend at least 10% of their total loan provisions to the agriculture applicants to show their strong support in this vital sector. Finally, the collaboration between banks and SME Corp. Malaysia under guidance of banking regulators is needed to be encouraged because the problem of asymmetric information between bank and farmer can be reduced through credit bureaus.